Numerical study using FE simulation on rectangular RC beams with vertical circular web openings in the shear zones. (1st November 2019) - Sayed, Ahmed M.
Highlights: The FE modeling can be used to calculate the shear capacity of RC beams. The FE modeling can be used to predict the failure modes of RC beams. By increasing the vertical circular opening diameter, the deflection decreases. By increasing the vertical circular opening diameter, the ultimate load decreases. The effect of opening diameter is greater than the effect of the number of openings. Abstract: Transverse and vertical openings are usually created in beams made of reinforced concrete (RC) to accommodate the pipes and ducts used in utilities. The decrease in shear strength because of the openings causes problems in current RC beams. This study investigates the impact of various vertical circular web openings alongside the shear-area span of an RC beam on its shear performance. To this end, a model with three finite element (FE) dimensions was developed, primarily for investigating and analyzing the outcome of this case. Using the ANSYS-V15 FE program, 41 beams were analyzed. The findings of the eight investigational beams were compared with results from previously published works. The devised model was tested to ensure its accurate functioning, using outcomes already attained through experiments. The outcomes of the experimental test proved that the newly devised FE model could be used to calculate the RC beams' shear-load capacity and to accurately predict failure modes. The outcomes revealed that the effect of the vertical-opening diameter on the width of the beam section was greater than the effect of the length of the shear span. Therefore, we concluded that the influence of the opening diameter was greater than the effect of the number of openings.